Implementing Character Education for Students with Behavioral Challenges: A Case Study at Yappen Rays Maritime Vocational School, Maumere - Wahyuningsih; Muis Kasim, Abdullah; Yati, Kristina (The Indonesian Institute of Science and Technology Research, 2025)
This study investigates the implementation of character education for students with behavioral challenges at Yappen Rays Maritime Vocational School, Maumere. The primary objectives are to examine how educators apply character education to address disciplinary issues and to identify the inhibiting factors in its implementation. Employing a descriptive qualitative approach, the study involved the school principal, duty teachers, the vice principal for student affairs, guidance and counseling teachers, security officers, civic education teachers, and students as research subjects. Data were collected through observation, interviews, and documentation, and analyzed through data presentation and conclusion drawing. The findings indicate that the school’s efforts through religious education, habituation practices, written warnings, and sanctions for latecomers have been relatively effective in reducing disciplinary violations, particularly tardiness. However, challenges remain due to external factors, including family background, residential environment, and internal factors, such as students’ personal attitudes and family income.